Differences in The Effects Of 15% Moringa Leaf (Moringa oleifera) Extract Gel and 70% Kecemcem (Spondias pinnata) Tree Bark Extract Gel on The Number of Gingiva Fibroblasts In Wistar Rats Postcurettage With Periodontitis Conditions - Ramadhany, Eka Pramudita; Susilahati, Ni Luh Desy Ayu; Dewi, Ni Putu Vania Amelia (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Periodontitis is a prevalent global oral disease leading to increased dental tourism, including to Indonesia. One treatment for periodontitis is gingival curettage with adjuvant therapy to speed up wound healing. Studies suggest that moringa leaf extract and kecemcem tree bark contain active compounds with anti-inflammatory and antioxidant properties. This study compares the effects of 15% moringa leaf extract gel and 70% kecemcem tree bark extract gel on the number of gingival fibroblasts in Wistar rats after curettage under periodontitis conditions. Material and Methods: Wistar rats were divided into four groups: positive control (hyaluronic acid), negative control (CMC-Na), 15% moringa leaf treatment, and 70% kecemcem tree bark treatment. Periodontitis was induced by tying a silk thread to the mandibular side, followed by curettage with a Sub-Zero (Osung) curette. The rats were euthanized on days 3, 5, and 7. Histological preparations were made, and fibroblast counts were taken from three fields of view using a light microscope at 400x magnification. Results and Discussion: The average number of fibroblasts in the kecemcem tree bark treatment group was higher than in the moringa leaf treatment group. The Least Significant Difference Post Hoc test showed a significant difference (p < 0.05). Flavonoids, phenols, and β-sitosterol in kecemcem tree bark were more effective in increasing fibroblast numbers compared to moringa leaf extract, as indicated by the higher average fibroblast count. Conclusion: 70% kecemcem tree bark extract gel had a more significant effect than 15% moringa leaf extract gel in increasing gingival fibroblasts in Wistar rats after curettage with periodontitis.